Nondestructive Determination of Chromium, Nickel, and Zinc in Neem Leaves and Facial Care Products by Laser Induced Breakdown Spectroscopy (LIBS). (13th April 2022) - Rehan, Imran; Gondal, Mohammed A.; Rehan, Kamran; Sultana, Sabiha; Khan, Saranjam; Rehman, Mujeeb Ur; Waheed, Abdul; Salman, Syed Muhammad
Abstract: Laser-induced breakdown spectroscopy (LIBS) was employed to determine Cr, Ni, and Zn in Neem-based beauty soaps and Neem leaves. The measurements were accomplished by attaining the optically thin plasma under the condition of local thermodynamic equilibrium (LTE) using standard calibration curve (SCC)-LIBS. The detection system was calibrated for these elements. The results showed 5.0 to 12 ppm by mass of nickel and 9.0 to 16 ppm by mass of chromium, which are above the secure allowed levels of these elements. Similarly, zinc was present from 6.2 to 14 ppm. The relative accuracy of LIBS was compared to inductively coupled plasma – optical emission spectrometry (ICP-OES) was from 0.1 to 0.3 with 2.5% error confidence.